Urban Interactions (punctum books, 2021)
"This volume is dedicated to eliciting the interactions between localities across late antique and early medieval Europe and the wider Mediterranean. Significant research has been done in recent years to explore how late “Roman” and post-“Roman” cities, towns and other localities communicated vis-à-vis larger structural phenomena, such as provinces, empires, kingdoms, institutions and so on. This research has contributed considerably to our understanding of the place of the city in its context, but tends to portray the city as a necessarily subordinate conduit within larger structures, rather than an entity in itself, or as a hermeneutical object of enquiry. Consequently, not enough research has been committed to examining how local people and communities thought about, engaged with, and struggled against nearby or distant urban neighbors.